Comparison of artificial intelligence algorithm for the diagnosis of hip fracture on plain radiography with decision-making physicians: a validation study - Salih Beyaz; Sahika Betul Yayli; Ersin Kılıç; Kutay Kılıç (Acta Orthopaedica et Traumatologica Turcica, 2024)
Objective: This study aimed to compare an algorithm developed for diagnosing hip fractures on plain radiographs with the physicians involved in diagnosing hip fractures.